Urban Forced Eviction: Experiences in the Metropolitan City of Lagos, Nigeria - Ayobami Abayomi Popoola; Michael Olaitan Olatunde; Hangwelani Hope Magidimisha; Abiodun Amuda; Bamiji Michael Adeleye; Lovemore Chipungu (Faculty of Geography, Universitas Gadjah Mada, 2020)
Urban poverty coupled with housing shortages have contributed to the proliferation of informal settlements and slums. This is one of the complex problems arising out of urbanization and which is piling pressure on urban authorities to use unorthodox methods (such as forced evictions) to ameliorate the situation. This paper revisits the use of forced migration in Badia East Community of Lagos city. Using the human security concept as a framework for analysis, the paper chronicles how urban forced migration is used as a tool to relocate the vulnerable urban poor by urban authorities in their bid to achieve sustainable development. Critical insight into the nature of these migrations was achieved by gathering data using the mixed approach. Finding from the study revealed rampant human abuse through the use of force during the eviction process. The paper concludes by recommending that the government should use best practices, (such as adequate government-assistance) during relocations and rehousing option explored.